An Improved Fire Fly Algorithm to Solve Economic Load Dispatch Problem including Practical Constraints - Karthikeyan, M.; Renga Raja, T.Sree (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The main objective of Economic Load Dispatch Problem of power generation is to schedule the committed generating units optimally so as to meet the required load demand while satisfying all the units with equal and inequality constraints. In this Paper an improved firefly algorithm has been implemented for the solution of economic load dispatch problem with non-smooth fuel cost curves considering the transmission loss coefficients and emission cost coefficientsbased on new version of firefly algorithm.Itis one of the evolutionary algorithm which is inspired by the idealized behavior of flashing characteristics of firefly to identify the nearest one. This approach considers the direct fireflies movement to global best if there is only one best solution in and around them. The effectiveness of the proposed method has been implemented to IEEE standard test system that demonstrates the capability of this approach in generating non dominated solutions of multi objective Economic Load Dispatch Problem.